What Drives Diversity in Social Recognition Mechanisms? - Tumulty, James P.; Sheehan, Michael J. (Frontiers in Ecology and Evolution, 2020)
Recognition allows animals to categorize social partners and differentiate among them in adaptive ways. Recognition systems are a fundamental component of social interactions, and a major goal for behavioral and evolutionary ecology is to understand the factors that influence the diversity of traits involved in social recognition across species and contexts. Here we argue that recognition is best understood as the interaction between a population of diverse senders and receivers with different perspectives and experiences. Receivers vary in the extent to which they agree on the category membership of senders and this variation is a key parameter that may explain the diverse evolutionary pressures shaping recognition systems. High receiver agreement (e.g., sex recognition) should favor uniformity in signals and innate recognition templates in receivers, while low receiver agreement (e.g., neighbor recognition) should tend to favor diversity in signals and flexible learning in receivers. Further, variation in how specifically receivers categorize senders may constrain the evolution of signals that need to function for multiple audiences. It remains an open question how receivers integrate multiple signals of different types of social categories. By framing recognition systems in a population context we hope this perspective will help spur new efforts to model and empirically investigate the mechanisms underlying the diversity of recognition systems across animals.